Pelaksanaan Kurikulum Tingkat Satuan pendidikan Pada MTs Negeri 1 Provinsi Jawa Timur - Mulyani Mudis Taruna (Balai Penelitian dan Pengembangan Agama Semarang, 2009)
The focus of this research is the implementation KTSP and factors thatsupport and hinder the implementation of the MTs KTSP Malang I. This re-search uses a qualitative approach with case studies. The results showed,that in general the implementation KTSP accordance with the standardsprovided by BSNP. Success in the implementation of KTSP is heavily infu-enced by human resources professionals and teachers who are committed tothe progress of the madrasah. Some constraint factors inhibiting the com-munication are the less fuent in the management of KTSP.Keywords: Curriculum, KTSP, Implementation KTSP